Eye Infections Caused by Filamentous Fungi: Spectrum and Antifungal Susceptibility of the Prevailing Agents in Germany - Walther, Grit (J Fungi (Basel), 2021)
Fungal eye infections can lead to loss of vision and blindness. The disease is most prevalent in the tropics, although case numbers in moderate climates are increasing as well. This study aimed to determine the dominating filamentous fungi causing eye infections in Germany and their antifungal susceptibility profiles in order to improve treatment, including cases with unidentified pathogenic fungi. As such, we studied all filamentous fungi isolated from the eye or associated materials that were sent to the NRZMyk between 2014 and 2020. All strains were molecularly identified and antifungal susceptibility testing according to the EUCAST protocol was performed for common species. In total, 242 strains of 66 species were received. Fusarium was the dominating genus, followed by Aspergillus, Purpureocillium, Alternaria, and Scedosporium. The most prevalent species in eye samples were Fusarium petroliphilum, F. keratoplasticum, and F. solani of the Fusarium solani species complex. The spectrum of species comprises less susceptible taxa for amphotericin B, natamycin, and azoles, including voriconazole. Natamycin is effective for most species but not for Aspergillus flavus or Purpureocillium spp. Some strains of F. solani show MICs higher than 16 mg/L. Our data underline the importance of species identification for correct treatment.